2014
DOI: 10.4102/sajpsychiatry.v20i2.533
|View full text |Cite
|
Sign up to set email alerts
|

Referral and collaboration between South African psychiatrists and religious or spiritual advisers: Views from some psychiatrists

Abstract: Corresponding author: A B R Janse van Rensburg (bernardj@gpg.gov.za) Background. Referral between psychiatrists and spiritual workers (e.g. Christian pastoral care workers, traditional healers, imams, rabbis and others) in the heterogeneous South African (SA) society is complicated and requires investigation to establish appropriate norms. Objective. To capture the views of some local psychiatrists on referral and collaboration between SA psychiatrists and religious or spiritual advisers. Methods. This expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…This also suggests that occupational therapists may need to have continuous professional development and workshops in relation to spirituality in order to understand clients' spiritual needs. These findings support the studies which reported that occupational therapy professionals and other healthcare professionals need to be aware of the clients' spiritual needs in order to refer the client to the relevant members of the interdisciplinary team 7,15,29,30,31 . Factor 4 (Clients' spiritual needs) had two variables related to spirituality which involve clients' and clinician responsibilities.…”
Section: Clients' Spiritual Needssupporting
confidence: 88%
See 4 more Smart Citations
“…This also suggests that occupational therapists may need to have continuous professional development and workshops in relation to spirituality in order to understand clients' spiritual needs. These findings support the studies which reported that occupational therapy professionals and other healthcare professionals need to be aware of the clients' spiritual needs in order to refer the client to the relevant members of the interdisciplinary team 7,15,29,30,31 . Factor 4 (Clients' spiritual needs) had two variables related to spirituality which involve clients' and clinician responsibilities.…”
Section: Clients' Spiritual Needssupporting
confidence: 88%
“…The differences in the factor loading for this factor could be explained by understanding the contextual factor of the respondents such as racial beliefs, culture, and ethnicity. These support Janse van Rensburg et al 7 who reported that the South African population is multi-cultural, multi-religious and spiritually diversified. However, some of these contextual factors might make addressing spirituality challenging for the students.…”
Section: Clients' Spiritual Needssupporting
confidence: 82%
See 3 more Smart Citations